The pro-inflammatory and anti-inflammatory cytokine profile in peripheral blood of women with recurrent implantation failure. Issue 6 (December 2015) - Liang, Pei-Yan; Diao, Liang-Hui; Huang, Chun-Yu; Lian, Ruo-Chun; Chen, Xian; Li, Guan-Gui; Zhao, Jin; Li, Yu-Ye; He, Xue-bing; Zeng, Yong
Abstract: Limited information is available on the balance state of pro- and anti-inflammatory cytokines in patients with recurrent implantation failure (RIF). This study assessed the pro- and anti-inflammatory cytokines in plasma of 34 patients with RIF, compared with those of 25 women with a successful pregnancy in the first IVF/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI–ET) cycle. The IFN-γ, IL-1β, IL-6 and IL-4 concentrations were higher, whereas the TGF-β1 concentration was lower in the RIF group compared with the control group. Furthermore, the ratios of pro-inflammatory and anti-inflammatory cytokines IFN-γ/IL-4, IFN-γ/IL-10, IFN-γ/TGF-β1, IL-6/IL-10, IL-6/TGF-β1, IL-1β/TGF-β1 and TNF-α/TGF-β1 were higher in the RIF group (all P < 0.01). The results suggested a shift toward a pro-inflammatory state in peripheral blood of the patients with RIF.